2019
DOI: 10.1016/j.csbj.2019.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae capsule polysaccharide as a target for therapeutics and vaccines

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 86 publications
0
56
0
Order By: Relevance
“…Recently, many reports studying polysaccharides of natural origin have indicated that there are a variety of biological functions, such as anti-tumor, immune stimulation, antibacterial, anti-oxidant, with various polysaccharides (Song et al, 2008;Chen et al, 2010Chen et al, , 2019Opoku-Temeng et al, 2019;. The antitumor effect of these polysaccharides is mainly exerted by regulating the host's immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many reports studying polysaccharides of natural origin have indicated that there are a variety of biological functions, such as anti-tumor, immune stimulation, antibacterial, anti-oxidant, with various polysaccharides (Song et al, 2008;Chen et al, 2010Chen et al, , 2019Opoku-Temeng et al, 2019;. The antitumor effect of these polysaccharides is mainly exerted by regulating the host's immune function.…”
Section: Discussionmentioning
confidence: 99%
“…The polysaccharide capsule of K. pneumoniae protects the pathogen from host cellmediated killing and the bactericidal effect of serum, thus contributing to K. pneumoniae pathogenicity (12). Studies examining the efficacy of antibodies (Abs) directed against CR-Kp CPS have demonstrated their potency in human cells and animal models (13)(14)(15)(16)(17), and CPS vaccines have the potential to prevent or moderate the severity of CR-Kp infection in monkeys and decrease the prevalence and emergence of resistant strains (14,(18)(19)(20). However, it is unknown if natural antibody responses to K. pneumoniae rely on anticapsular responses.…”
mentioning
confidence: 99%
“…The rise in carbapenem-resistant K. pneumoniae infections in hospitals and its associated morbidity and mortality 43 has led to increased interest in alternative control strategies such as vaccines, phage therapy and antibody therapy, key targets for which are the K and O surface antigens 44,45 . Kleborate confidently identified K and O biosynthesis loci in 98.3% and 99.1% of EuSCAPE genomes, respectively, including 87 distinct K loci and 11 distinct O loci ( Figures S2 and S3 ).…”
Section: Resultsmentioning
confidence: 99%